The Desert of Wheat - Grey, Zane (Saga Egmont, 2022)
A classic portrait of America during World War I, from American author Zane Grey, famously known for his romanticized stories about the old West.\'The Desert of Wheat\' (1919) sets the tone for a nation\'s anxiety at the brink of a century of change. It is a 20th century tale of romance and sabotage, describing the effect war has on a country and its people. Grey has written a classic Western with a patriotic and anti-union propaganda twist, recounting a country divided.